Колективний суб’єкт і правовідносини у кримінальному праві України (проблеми теорії) - Гусаров, С. М.; Gusarov, S. M.; Сергій Гусаров (Вісник Кримінологічної асоціації України. - 2015. - № 2 (10). - С. 7-16, 2015)
У статті розглянуто проблеми теорії правовідношення у кримінальному праві України. Визначено напрямки її розвитку із урахуванням передбаченого законодавством інституту застосування до юридичної особи заходів кримінально-правового характеру. Показано відмінності кримінально-правових відносин за участю юридичних осіб від правовідносин негативної кримінальної відповідальності.

Criminal and legal regulation as one of the means of managing social relations, ensuring the regulation of the latter and protection of the positive interests of their members and operates and is being developed in accordance with the prevailing for a particular period of time doctrinal and ideological concepts, which are the basic for the subjects of rule-making and branch legal enforcement. One of the axioms of the modern theoretical and practical law, based largely on the ideas of legal positivism is the thesis according to which law norms, including criminal one are realized only within legal relations. The most efficient the theory of legal relations in criminal and legal doctrine is developed in connection with the phenomenon of negative criminal liability. In criminal and legal theory different kinds and types of branch legal relations are distinguished. Herewith, first of all, special attention is paid to the legal fact, which generates them. Subjective composition of the legal fact affects the type of legal relations, besides the generated legal fact itself. Party (subject) of any legal relation in criminal law is always the state represented at the level of individual legal regulation by specifically authorized authorities responsible for keeping public order or justice. Another subject of the vast majority of legal relations in criminal law is an individual (in legal relations of negative criminal liability, legal relations on compulsory medical measures, in criminal legiti- mate behavior). After the alteration of the General Part of the Criminal Code of Ukraine, namely with the Section XIV-1 the continuum of persons who may be involved in security relations within criminal law has significantly expanded. Legal relations, where the state interacts with the collective subject and which are regulated by criminal law and aimed at strengthening the protection of certain objects of criminal and legal protection (national security, public safety, areas of official activity, peace and security of mankind), have become objective legal reality. Criminal and legal relationship involving legal entities have a number of features; do not coincide with any other legal relations, which have been regulated by domestic criminal law.

В статье рассмотрены проблемы теории правоотношений в уголовном праве Украины. Определены направления ее развития с учетом предусмотренного законодательством института применения к юридическим лицам мер уголовно-правового характера. Показаны различия уголовно-правовых отношений с участием юридических лиц от правоотношений негативной уголовной ответственности.
Keywords: Кримінальне право. Criminal Law. Уголовное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; кримінально-правові відносини; юридичний факт; злочин; юридична особа; заходи кримінально-правового характеру; criminal and legal relations; legal fact; crime; legal enteties; measures of criminal and legal nature; уголовно-правовые отношения; юридический факт; преступление; юридическое лицо; меры уголовно-правового характера